The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4103/ijciis.ijciis_27_17
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder after myocardial infarction and coronary artery bypass grafting

Abstract: Post traumatic stress disorder is a psychiatric disease that is usually precipitated by life threatening stressors. Myocardial infarction, especially in the young can count as one such event. The development of post traumatic stress after a coronary event not only adversely effects psychiatric health, but leads to increased cardiovascular morbidity and mortality. There is increasing evidence that like major depression, post traumatic stress disorder is also a strong coronary risk factor. Early diagnosis and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Higher quality of life level along with the absence of posttraumatic symptoms can be recognized as an indicator of adaptation to the new reality of life with demands and limitation of one's state of health and effective psychological coping in a situation of the sudden collapse of one's capabilities and sense of security. On the other hand, a manifestation of PTSD symptoms and reduced quality of life may contribute to an increased risk of another heart attack and mortality (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Higher quality of life level along with the absence of posttraumatic symptoms can be recognized as an indicator of adaptation to the new reality of life with demands and limitation of one's state of health and effective psychological coping in a situation of the sudden collapse of one's capabilities and sense of security. On the other hand, a manifestation of PTSD symptoms and reduced quality of life may contribute to an increased risk of another heart attack and mortality (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Affective disorders characterized by immense psychological trauma, such as war-related PTSD, are associated with cardiovascular disorders [ 6 , 28 ]. Such disorders exert their effect through sympathetic overstimulation, hypothalamic-pituitary-adrenal axis dysregulation, and promoting immune-inflammatory dysfunction [ 6 , 7 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Affective disorders characterized by immense psychological trauma, such as war-related PTSD, are associated with cardiovascular disorders [ 6 , 28 ]. Such disorders exert their effect through sympathetic overstimulation, hypothalamic-pituitary-adrenal axis dysregulation, and promoting immune-inflammatory dysfunction [ 6 , 7 , 28 ]. Furthermore, PTSD is associated with behavioral alternations such as increased smoking or increased alcohol consumption, which acts as potentiating factors to CAD development [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…AMI is a stressful traumatic event, and AMI patients usually have a severe psychologically traumatic experience that endangers their lives. Recently, an increasing number of studies have explored AMI-related PTSD ( Edmondson et al, 2011 ; Perkins-Porras et al, 2015 ; Singh et al, 2017 ; Birk et al, 2019 ). Previous study ( Meli et al, 2019 ) showed that invasive treatment was a risk factor for PTSD in AMI patients, and AMI patients that received invasive surgery were more prone to develop PTSD symptoms than those that received conservative treatment.…”
Section: Introductionmentioning
confidence: 99%